Fish communities across a spectrum of habitats in the western Beaufort Sea and Chukchi Sea. (August 2015) - Logerwell, E.; Busby, M.; Carothers, C.; Cotton, S.; Duffy-Anderson, J.; Farley, E.; Goddard, P.; Heintz, R.; Holladay, B.; Horne, J.; Johnson, S.; Lauth, B.; et al.
Highlights: Chinook Salmon may be moving into the Arctic. Nearshore is important habitat for forage fish (e.g., Pacific Herring and Capelin). Nearshore is a nursery area for other species (e.g., Arctic Cod and Saffron Cod). Commercially important gadids are present but not likely spawning in the Arctic. Conceptual models of Arctic and Saffron Cod life history distribution are provided. Abstract: The increased scientific interest in the Arctic due to climate change and potential oil and gas development has resulted in numerous surveys of Arctic marine fish communities since the mid-2000s. Surveys have been conducted in nearly all Arctic marine fish habitats: from lagoons, beaches and across the continental shelf and slope. This provides an opportunity only recently available to study Arctic fish communities across a spectrum of habitats. We examined fish survey data from lagoon, beach, nearshore benthic, shelf pelagic and shelf benthic habitats in the western Beaufort Sea and Chukchi Sea. Specifically, we compare and contrast relative fish abundance and length (a proxy for age) among habitats and seas. We also examined ichthyoplankton presence/absence and abundance of dominant taxa in the shelf habitat. Our synthesis revealed more similarities than differences between the two seas. For example, our results show that the nearshore habitat is utilized by forage fish across age classes, and is also a nursery area for other species. Our results also indicated that some species may be expanding their range to the north, for example, Chinook Salmon. In addition, we documented the presence of commercially important taxa such as Walleye Pollock and flatfishes (Pleuronectidae). Our synthesis of information on relative abundance and age allowed us to propose detailed conceptual models for the life history distribution of key gadids in Arctic food webs: Arctic and Saffron Cod. Finally, we identify research gaps, such as the need for surveys of the surface waters of the Beaufort Sea, surveys of the lagoons of the Chukchi Sea, and winter season surveys in all areas. We recommend field studies on fish life history that sample multiple age classes in multiple habitats throughout the year to confirm, resolve and interpret the patterns in fish habitat use that we observed.